Posição sistemática de quatro espécies de Cyrtoneurina Giglio-Tos (Diptera, Muscidae) - Couri,Márcia Souto (2000)
The systematic position of four species considered as Cyrtoneurina in Carvalho et al. (1993) - C. alifusca Couri, 1982; C. brunnea (Hough, 1900); C. pallipes Stein, 1918 and C. scutellata Johnson, 1919 are discussed. These species were originally described, respectively, in Cyrtoneurina, Muscina, Cyrtoneurina and Clinopera. The detailed analysis of the morphology, especially of the terminalia, enabled the transference of C. brunnea and C. pallipes to Cyrtoneuropsis and C. scutellata to Neomuscina, all are new combinations, and the confirmation of C. alifusca in the Cyrtoneurina. The morphology of the terminalia is described and illustrated. The lectotype of Cyrtoneuropsis pallipes (Stein, 1918) is herein proposed.